2020
DOI: 10.1017/s0959270920000027
|View full text |Cite
|
Sign up to set email alerts
|

Potential distribution of a climate sensitive species, the White-winged Snowfinch Montifringilla nivalis in Europe

Abstract: Summary The White-winged Snowfinch Montifringilla nivalis nivalis is assumed to be highly threatened by climate change, but this high elevation species has been little studied and the current breeding distribution is accurately known only for a minor portion of its range. Here, we provide a detailed and spatially explicit identification of the potentially suitable breeding areas for the Snowfinch. We modelled suitable areas in Europe and compared them with the currently known distribution. We built a distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…At the study area scale, climatic variables, together with terrain roughness and elevation, appeared to be the main limiting factors for the potential distribution of alpine species. This is consistent with what has been previously recorded in alpine birds (Brambilla et al 2020), but also in other taxa such as plants (Pauli et al 2012) or insects (Wilson et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…At the study area scale, climatic variables, together with terrain roughness and elevation, appeared to be the main limiting factors for the potential distribution of alpine species. This is consistent with what has been previously recorded in alpine birds (Brambilla et al 2020), but also in other taxa such as plants (Pauli et al 2012) or insects (Wilson et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Given that the European atlas has a 50-km resolution and that BirdLife distribution shapefiles are meant to be used at a coarse resolution, and are therefore sometimes not accurate for mountain species (cf. Brambilla, Resano-Mayor, et al, 2020), we performed a qualitative assessment of the consistency between observed and predicted distribution. Models that correctly predict the occurrence patterns of a species over distant sites, such as other mountain regions or neighboring areas, could be considered as more reliable and useful for extrapolation over different contexts (including over different time periods) than models that perform poorly when projected outside the calibration area.…”
Section: Model Evaluationmentioning
confidence: 99%
“…Therefore, we adopted a maximum entropy approach, as implemented in Maxent, as this method outperforms others when non-standardized data are used [42,43]. Maxent works with an occurrence-background framework, and it is essential to place background points, to mirror the environmental conditions that had been sampled with data collection (i.e., to avoid the inclusion into the background of conditions where the target species had not been found just because such conditions were not sampled) [44]. In our study, we did not have any information about the sampling efforts, so we restricted the background to the areas containing occurrence records by creating a 20 km buffer around the occurrence records, within which we randomly placed 30,000 points.…”
Section: Species Distribution Modellingmentioning
confidence: 99%